Development of heuristic optimization methods and experimental simulation design for the components and resources of healthcare - Atalan, Abdulkadir (My University, 2019)
Sağlık sektörü, üretim dışında en büyük ve en hızlı büyüyen sektörlerden biridir. Çoğu ülkede, özellikle ABD’de küresel veya yerel bir sağlık sistemi bulunmamakla birlikte, sağlık hizmetleri için benzersiz ve karmaşık bir sistem bulunmaktadır. Bu karmaşıklık, kalitesiz hizmet, duplikasyonlar, yanlış̧ tedavi, yüksek bekleme süresi, ilaç hatası vb. gibi birçok soruna neden olmaktadır. Dünyada var olan sağlık sistemlerinde, sağlık kuruluşlarına ait iki tür sorun vardır. Birincisi, devlet sağlık kuruluşlarında hastaların tedavi olmak için bekleme süreleri çok yüksek olmaktadır. Bu nedenle hasta memnuniyetsizliği ve devlet sağlık harcamaları orantısız bir şekilde artmaktadır. İkinci problem ise özel sağlık kurumlarına aittir. Bu tür sağlık kuruluşlarında hastaların bekleme zamanı düşüktür ancak hastanın ödeyeceği tedavi maliyeti yüksektir. Bu, hastaların daha az beklemek için cebinden daha çok para ödemeleri gerektiği anlamına gelmektedir. Bu nedenle özel sağlık kurumlarında yıllık tedavi edilen hasta sayısı azalmaktadır ve yıllık gelirleri düşmektedir. Bu tür problemleri çözmek için iyi tanımlanmış matematiksel modelleme ile mantıklı bir çözüm elde etmek için optimizasyon yöntemi olarak bilinen sezgisel bir metot kullanımı kaçınılmaz olmaktadır. Dünyada sağlık sisteminde iki yapı vardır; bunlar devlet ve özel sağlık sistemleridir. Sağlık sistemlerini oluşturan birçok bileşenler bulunmaktadır. Özellikle hastalar, devletler (sağlık hizmetleri için ana kuralları ve yasaları yapan), sağlık hizmeti verenler ve özel sağlık sektörleri (özel sağlık sigorta şirketleri, özel hastaneler, özel sağlık sektörü çalışanları) sağlık sisteminin merkezinde yer almaktadır. Bu tez üç ana kısımdan oluşmaktadır. Tezin ilk kısmını oluşturan bölümde, sağlık sistemleri hem tekel düzeyde hem de etkileşimli olarak ele alınması ile optimizasyon modelleri geliştirilerek karşılaştırma yapılmıştır. Sağlık sistemleri için geliştirilen sezgisel matematiksel modellerde optimum sonuçların elde edilmesi amaçlanmıştır. Tezin ikinci bölümü ise sağlık hizmeti veren kuruluşlara ait sağlık kaynaklarının yönetimi ile alakalıdır. Stratejiler geliştirilerek sağlık sitemlerine ait kaynakların optimum sayısını elde etmek için deney tasarımı (DOE) tekniğinden yararlanılarak kesikli-olay-simülasyon modellemesi yapılmıştır. Sağlık sistemleri stokastik bir yapıya sahip oldukları için genellikle matematiksel modellemeler kapalı formüller ile ifade edilmektedir. Açıkça matematiksel olarak modellenemeyen sistemlerin simülasyon tekniklerini kullanmak yaygındır. Ancak, bu çalışma ile kaynaklara ait senaryolar oluşturularak her bir durum için sezgisel matematiksel modellemeler geliştirilmiştir. Böylelikle, hastaların bekleme süreleri en aza indirilerek tedavi edilen hastaların sayısını maksimuma çıkarılması amaçlanmıştır. Bu bölüme ek olarak, Türkiye’deki acil servislerinde uzman hemşire istihdamı ile acil servislerdeki yoğunluğun azaltılmasına yönelik bir simülasyon modeli geliştirilmiştir. Üçüncü bölümde, ülkelere ait sağlık sistemlerinin kalitesi sorgulanmıştır. Kişi başına düşen gayri safi milli hasılası 10.000 ABD dolarını aşan 53 ülkeyi kapsayan bir küresel sağlık rekabet endeksini (GHCI) oluşturmak için istatistiksel optimizasyon modeli geliştirilmiştir. Bu çalışmada, GHCI hastaların sağlık kuruluşlarında hizmet alma kolaylığını veya zorluğunu belirten bir indeks olarak tanımlanıştır. GHCI üzerinde etkili olduğu düşünülen faktörler belirlenmiş ve anlamlılık düzeyleri istatistiksel olarak analiz edilmiştir. Geliştirilen yöntemler aracılığıyla elde edilen verilere göre sağlık sisteminin içinde yer alan karar değişkenleri için senaryolar ve kriterler karşılaştırılarak en iyi çözümler elde edilmiştir. Tezin her üç kısmında, elde edilen sonuçlar ile sağlık sisteminin içinde yer alan bütün bileşenlerin fayda görmesi sağlanmıştır. Sağlık sistemlerin merkezinde yer alan ''hasta'' faktörünün daha çok fayda görmesi hedeflenmiştir

Healthcare is one of the largest and fastest growing businesses besides manufacturing. Most of the countries, especially the U.S. do not have a global or local healthcare system but have a unique and complex system for healthcare service and delivery. This complexity causes many problems such as poor-quality service, duplicates, wrong treatment, high waiting time, medication error, etc. In health systems around the world, there are two types of problems that belong to health institutions. First, the waiting times for treating patients in public health facilities are very high. For this reason, patient dissatisfaction and state health spending are increasing disproportionately. The second problem belongs to private health institutions. In such health institutions, the waiting time of the patients is low, but the cost of the treatment is high. This means that patients have to pay a lot of money from their pocket to wait less. Because of this, the number of patients treated annually in private health institutions is decreasing and their annual income is decreasing. In order to solve such problems positively, the use of optimization method which is mathematical modelling is inevitable. This thesis consists of three chapters.There are two structures in healthcare system worldwide; these are public and private healthcare systems. There are many components that built up health systems. Especially, patients, governments as the main rules and laws maker for health care, healthcare providers and private healthcare sectors (private healthcare insurance companies, private hospitals, resources of private healthcare) are at the center of the healthcare system. In the section that constitutes the first part of the thesis, optimization models are developed by comparing healthcare systems both at the monopoly level and interactively. Intuitive mathematical models developed for health systems aim to achieve optimum results.The second part of the thesis is related to the management of healthcare resources. The aim of this research is to apply discrete event simulation approach based on optimization modelling and design of experiment (DOE) technique to derivate strategies and analyze situations to find optimum solutions in a healthcare department. Since healthcare systems have a stochastic structure, mathematical modeling is usually expressed by closed formulas. It is common to use simulation techniques of systems that cannot be mathematically modeled explicitly. However, with this study, the scenarios of the resources were created, and intuitive mathematical models were developed for each situation. Thus, the objectives of these applications are the minimization the waiting time of the patients, and the maximization the number of treated patients. In addition to this section, a simulation model to reduce the density of the emergency service with advanced nurses employed in the emergency services have been developed in Turkey.In the third chapter, the quality of health systems of countries is questioned. A statistical optimization model has been developed to create a global healthcare competitiveness index (GHCI) covering 53 countries with a gross domestic product per capita of over US $ 10,000. GHCI determines the ease or difficulty of receiving services for patients from healthcare systems of considered countries. Factors considered to be influential on the GHCI were identified and significance levels were analyzed statistically. Then, the desirability equation that is formed in the factors has been established to form the objective function in the optimization model. This section of the thesis has determined the optimum values of the factors for countries to be able to compete in healthcare service. Having those factors with optimum values is an indicator of higher quality of healthcare systems.According to the data obtained through the developed methods, the best solutions were obtained by comparing the scenarios and criteria for the decision variables within the healthcare system. In all three parts of the thesis, all the components included in the healthcare system are benefited with the results obtained by this research. It is aimed that the patient factor is addressed in the center of healthcare systems was benefit more.
Keywords: Advanced Nurse; Bilgi teknolojileri; Deney Tasarımı; Design of Experiment; Devlet Sağlık Sistemi; Economic aspects; Economics, Medical; Ekonomi, Tıbbi; Ekonomik açıdan; Global Health Competitiveness Index; Health facilities; Health services administration; Health surveys; Heuristic Optimization Models; Information technology; Küresel Sağlık Rekabet İndeksi Public Healthcare System; Özel Sağlık Sistemi; Private Healthcare System; Sağlık araştırmaları; Sağlık Hizmetleri Yönetimi; Sağlık kuruluşları; Sezgisel Optimizasyon Modeli; Simulation; Simülasyon; Uzman Hemşire